Scientific life in the Andalusian city of Carmona (Journal of the College of Education for Women, 2026)
The study of medieval cities—regardless of their geographical location or civilizational context—has never been a simple or straightforward undertaking in historical research. A city represents a complex entity that embodies within its physical and symbolic structures the features of civilization and culture, patterns of daily life, and the social and economic relationships that shaped its community across successive periods. It is not merely a geographical space, but a living historical organism reflecting shifts in political authority, demographic transformations, intellectual and religious influences, as well as systems of production and urban development. Therefore, approaching the history of any medieval city requires a multidimensional perspective capable of capturing its political, social, and cultural contexts.The city of Carmona offers a representative example of such historical interaction. Throughout its successive eras, it experienced continuous political transformations due to the alternation of ruling powers, leaving a clear imprint on its urban features and social and cultural structures. The city underwent significant changes in administrative and defensive systems, while its geographical location contributed to shaping its strategic and economic role. This cumulative civilizational layering generated notable cultural, intellectual, and social diversity, manifested in patterns of daily life, scholarly and religious activity, and the interaction of its inhabitants with the wider regional environment. Accordingly, the study of Carmona provides valuable insight into the broader transformations that characterized medieval cities and illustrates the extent to which they were shaped by major political and civilizational developments within the Andalusian sphere.